2015
DOI: 10.1002/bse.1903
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Employees in Sustainable Development – a Case Study of Environmental Education and Awareness Training in Hong Kong

Abstract: Environmental education and awareness training can help to develop and encourage a transition to a greener corporate culture. A series of environmental education and awareness training programmes of The Hongkong and Shanghai Banking Corporation Limited (HSBC) (Hong Kong) was used as a case study to assess how learning transfers through nature-based environmental education and awareness training and to investigate the possible outcomes of providing nature-based training to employees. Evaluation of the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 57 publications
7
88
0
3
Order By: Relevance
“…The individual is also aware of how their environmental behavior contributes to sustainability (Fan, Fang, & Cer, ). A study conducted by Law, Hills, and Hau () found that thorough environmental knowledge enables an individual to determine a positive environmental behavior. Another study ascertained a positive correlation between an increase in environmental knowledge and an increase in environmental attitude and behavior that has benefited the environment (Haryanto, ; Hsu & Roth, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual is also aware of how their environmental behavior contributes to sustainability (Fan, Fang, & Cer, ). A study conducted by Law, Hills, and Hau () found that thorough environmental knowledge enables an individual to determine a positive environmental behavior. Another study ascertained a positive correlation between an increase in environmental knowledge and an increase in environmental attitude and behavior that has benefited the environment (Haryanto, ; Hsu & Roth, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental consciousness is an element of individual beliefs that guide consumers to conduct behavior beneficial to the environment (Abd'Razack et al, ). It has also been shown that those who have environmental consciousness also exhibited characters and attitudes such as loyalty and a strong sense of commitment (Law et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a consumption perspective, one crucial aspect of any sustainable food system is the relationships that it fosters (Carroll & Fahy, ; Kneafsey et al, ). Relationships are also paramount in forming and reinforcing organizational culture (Law et al, ). As well as fostering linkages with consumers and organizations, the catering service, whether in‐house or outsourced, also creates an important link between the organization and food producers and suppliers.…”
Section: Findings: the Importance Of Contextual Considerationsmentioning
confidence: 99%
“…As such, an increasing amount of organisations have implemented CSR strategies to improve pro-environmental attitudes, behaviour and habits of individuals in the workplace (Baumgartner & Winter, 2014;Law, Hills, & HangHau, 2017). Incorporating "CSR-Washing" into a company's environmental education can help to raise awareness and build consciousness of employees towards greenwashing and the multifarious consequences involved as well as on instruments and habits on how to avoid them.…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 99%
“…It would also address the gap between sustainable awareness/knowledge and the actual sustainable behaviour within organisations (Kollmuss & Agyeman, 2002), a problem also well-discussed in environmental psychology literature (e.g., Bamberg & Möser, 2007;Fietkau & Kessel, 1981). Overall, it would help to develop and encourage a transition to a greener corporate culture (Law, Hills, & HangHau, 2017).…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 99%